Servicing Land for Housing Development in Peri-Urban Areas of Kumasi, Ghana: Theory Versus Practice (Journal of Science and Technology, 2016)
Since the 1950s, developing countries have been experiencing phenomenal growth in urban population and this is reflected in high demand for housing and residential land. In Ghana, the rapid population growth of the national capital and the regional capital towns including Kumasi has brought to the fore the need for more land for residential development. However, the rate at which urban land is being released for housing development by the traditional authorities is not commensurate with the rate at which it is being serviced. This has created problems whereby residents in newly developing housing areas lack basic facilities and services. This paper examines the factors and problems militating against orderly development of infrastructure in the peri-urban housing areas in the Kumasi Metropolitan Area. The paper suggests interventions aimed at addressing the problems related to the provision of infrastructure and services in peri-urban settlements of Kumasi, Ghana.